Supraciliary Approach in Surgical Treatment of Zygomaticomaxillary Complex Fractures - K. T. Kokayev; A. V. Teremov; G. A. Zabunyan; A. A. Martirosyan; A. G. Baryshev; V. A. Porhanov (Инновационная медицина Кубани, 2024)
Objective: To demonstrate the effectiveness of a supraciliary approach in zygomaticomaxillary complex fractures treatment.Case report: Patient A. (33-year-old man) was admitted to the Scientific Research Institute – Ochapovsky Regional Clinical Hospital No. 1 (Krasnodar, Russian Federation) with a diagnosis of traumatic fractures of the right and left zygomaticomaxillary complexes. According to the medical history, the injury was caused by a car accident. The patient underwent computed tomography of the facial skeleton. Computed tomography findings: fractures of lateral and medial orbital walls, supraorbital and infraorbital rims, glabella, and nasal septum. The patient underwent repositioning of the bone fragments and internal fixation with metal implants. The glabella fracture was reduced through a supraciliary approach. The function of the mimic muscles was fully preserved. The configuration of the face and soft tissues was restored. No soft tissue edema was observed. The postoperative scar is visualized after the unfolding of the orbito-palpebral fold of the upper eyelid.Conclusions: The systematic use of esthetic approaches by surgeons completely changes the rooted traditional way of managing patients with various maxillofacial pathologies. In addition to outstanding esthetic results, it increases the surgeons’ expertise level and the range of tasks a comprehensively developed specialist is capable of dealing with. One of the most crucial aspects is improvement of patients’ quality of life.